2006
DOI: 10.1007/s10750-006-0144-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of fish communities along two estuarine gradients in southern Florida

Abstract: In tropical and subtropical estuaries, gradients of primary productivity and salinity are generally invoked to explain patterns in community structure and standing crops of fishes. We documented spatial and temporal patterns in fish community structure and standing crops along salinity and nutrient gradients in two subtropical drainages of Everglades National Park, USA. The Shark River drains into the Gulf of Mexico and experiences diurnal tides carrying relatively nutrient enriched waters, while Taylor River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…In comparison with other studies of tidal freshwater marsh during peak seasons (e.g. Rozas & Odum 1987, Castellanos & Rozas 2001, Green et al 2006, we caught about half the number of species and lacked transient species that occupy the marsh surface later during the season. The resident species in our study comprise a guild of omnivores that rapidly colonize the marsh surface once it is inundated, feeding on detritus, epiphytic bacteria, insect larvae, and infauna (Kneib 1997(Kneib , 2000.…”
Section: Nekton Diversity and Community Assemblycontrasting
confidence: 50%
See 1 more Smart Citation
“…In comparison with other studies of tidal freshwater marsh during peak seasons (e.g. Rozas & Odum 1987, Castellanos & Rozas 2001, Green et al 2006, we caught about half the number of species and lacked transient species that occupy the marsh surface later during the season. The resident species in our study comprise a guild of omnivores that rapidly colonize the marsh surface once it is inundated, feeding on detritus, epiphytic bacteria, insect larvae, and infauna (Kneib 1997(Kneib , 2000.…”
Section: Nekton Diversity and Community Assemblycontrasting
confidence: 50%
“…m -2 in flooded intertidal marsh sites. In 2 studies using a 1 m 2 throw trap in the Florida Everglades, Green et al (2006) reported mean densities of 6.6 ind. m -2 at freshwater sites in the Taylor River drainage, and Williams & Trexler (2006) documented mean fish densities of 21.6 ind.…”
Section: Nekton Densitiesmentioning
confidence: 99%
“…Mean standing crop within the natural estuary was similar to maximum values in Florida dwarf mangrove areas («4 g/m2) (Green et al 2006;Lorenz 1999) and less than…”
Section: Prey Availabilitymentioning
confidence: 56%
“…However, biomass was not significantly different between mesohaline and polyhaline environments in the same study region of the Everglades (Lorenz and Serafy 2006), where mangrove habitats are largely non-tidally dominated and oligotrophic relative to the riverine mangrove system, at the study site (Ewel 1998). Seasonal differences in biomass in Everglades mangroves may be more a function of hydrography, hydroperiod, and connectivity rather than salinity per se (Green et al 2006;Faunce et al 2004;Lorenz 1999). Although largely an invertebrate feeder, American flamingo food items increased in abundance during the wet season in the Celestun Lagoon in Yucatan, Mexico (Arrengo and Baldasarre 1999).…”
mentioning
confidence: 73%
“…Differences in native fish abundance between WC and MC canals likely reflect the variation in productivity of the marshes they bisect. WC canals connect to longer hydroperiod marshes almost year-round, which have been shown to have higher fish abundances relative to the shorter hydroperiod marshes that connect to MC canals only during the wet season (Chick et al 2004;Green et al 2006). Additionally, canal connectivity to marsh species pools with different community structure may also have contributed to the observed patterns in this Study.…”
Section: Hypothesized a Gradient In Novelty Inmentioning
confidence: 67%